Análise comparativa da composição química de cafés do cerrado mineiro e do sul de Minas Gerais - Alves, Blyeny Hatalita Pereira (2004)
Coffee (Coffea Arabica) is one of the agricultural products that drive agribusiness in the country. The 2002/2003 harvest recorded a total of 48480 thousand benefited bags, as well as being one of the most popular and most consumed beverages in the world. Due to its importance and presence in the daily life of all, it is necessary that the product is of quality and is expected to present pleasant characteristics of aroma and flavor. This dissertation presents the study of the chemical composition of coffees (Coffea Arabica) produced in the Cerrado Mineiro and Southern Minas Gerais, the main regions of the state, which is the largest coffee producer in the country. The coffee samples, previously classified in Mole, Duro, Riado and Rio, were roasted in the “roast americana” (weak) pattern and milled. House made. High performance liquid chromatographic analysis indicated that Mole coffees had higher values ​​of chlorogenic acids: 43.36 and 35.52 mg g'1 for cerrado and sul, respectively. The same was observed for the compounds: caffeine, 16.04 and 13.13 mg g ', trigonelline 15.60 and 12.20 mg g'1. Caffeic acid is present in amounts less than 1.82 mg g'1 in all samples. The volatile compounds identified by gas chromatography-mass spectrometry were subjected to principal component analysis (PCA) which allowed the indication of the substances (fifteen) with the largest participation in the discrimination in the samples, among them, 2-methylpyrazine, pyrrol, toluene. , the furfural, among others. The similarity matrix graph clearly shows the separation of the South and Cerrado Mole classification samples from the other samples. The results obtained in this study show that the best-rated coffees (Mole and Duro), and therefore of better quality, have a more expressive chemical composition than the lower-rated coffees (Riado and Rio), and come to contribute the studies, which aim to establish relationships between the current classification of the coffee (cup test) and its chemical composition, and provide data to characterize the coffee produced in the Cerrado and South of Minas Gerais.